2022
DOI: 10.1186/s12871-022-01858-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy of two doses of dexmedetomidine as an adjunct to levobupivacaine in infraclavicular brachial plexus block: prospective double-blinded randomized controlled trial

Abstract: Background This prospective, double-blind, randomized, controlled trial compared the efficacy of two dexmedetomidine doses (50 and 100-μg) combined with levobupivacaine on sensory block duration in infraclavicular brachial plexus block. We hypothesized that perineural dexmedetomidine would extend sensory block duration dose-dependently. Methods The study included 60 patients aged 20 to 60 years of both sex with an ASA I/II undergoing forearm and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…There was no difference in terms of the onset of motor block in our study (18.53 ± 5.59 minutes and 16.30 ± 3.62 minutes, respectively; p = 0.087), which is consistent with 13.0 ± 5.4 minutes and 13.8 ± 7.2 minutes, respectively (p = 0.924) [ 20 ]. Ghazaly et al [ 21 ] reported a mean duration of sensory of 14.55 hours and motor block of 15.6 hours in the patients undergoing ICBP with dexmedetomidine (100 mcg) plus levobupivacaine, which was similar to our findings.…”
Section: Discussionsupporting
confidence: 92%
“…There was no difference in terms of the onset of motor block in our study (18.53 ± 5.59 minutes and 16.30 ± 3.62 minutes, respectively; p = 0.087), which is consistent with 13.0 ± 5.4 minutes and 13.8 ± 7.2 minutes, respectively (p = 0.924) [ 20 ]. Ghazaly et al [ 21 ] reported a mean duration of sensory of 14.55 hours and motor block of 15.6 hours in the patients undergoing ICBP with dexmedetomidine (100 mcg) plus levobupivacaine, which was similar to our findings.…”
Section: Discussionsupporting
confidence: 92%